2019
DOI: 10.1016/j.sxmr.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology Update of Erectile Dysfunction in Eight Countries with High Burden

Abstract: Introduction Prior epidemiology studies on erectile dysfunction (ED) have varied in geography/place, time period, and methodology. Due to this variability, comparisons of data across studies are greatly limited. Additionally, little is known about the rates of comorbid ED and benign prostatic hyperplasia (BPH). Aim To update the prevalence of ED and patient characteristics using a single methodology in 8 countries: Brazil, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 37 publications
0
51
0
3
Order By: Relevance
“…According to the multinational Men's Attitudes to Life Events and Sexuality (MALES) study, the overall self‐reported prevalence of ED among men aged 20–‐75 years was estimated at 16% 2 . A recent retrospective cross‐sectional study of men aged ≥18 years from eight countries reported an overall self‐reported ED prevalence of 40.5%, with a higher estimated prevalence of 42.6% in the United Kingdom (UK) 3 . The prevalence and severity of ED increase with age, and prior research has consistently demonstrated that ED is normally the result of underlying cardiovascular or endocrine disease or depression 4 …”
Section: Introductionmentioning
confidence: 99%
“…According to the multinational Men's Attitudes to Life Events and Sexuality (MALES) study, the overall self‐reported prevalence of ED among men aged 20–‐75 years was estimated at 16% 2 . A recent retrospective cross‐sectional study of men aged ≥18 years from eight countries reported an overall self‐reported ED prevalence of 40.5%, with a higher estimated prevalence of 42.6% in the United Kingdom (UK) 3 . The prevalence and severity of ED increase with age, and prior research has consistently demonstrated that ED is normally the result of underlying cardiovascular or endocrine disease or depression 4 …”
Section: Introductionmentioning
confidence: 99%
“…Статистика ЭД по возрасту: ЭД поражает около 10% мужчин за десятилетие жизни. Например, 50% мужчин в возрасте старше 50 лет страдают ЭД [14].…”
Section: распространенность эдunclassified
“…Erectile dysfunction (ED) is a common, burdensome, and costly urologic condition with increasing prevalence as men age. It is estimated that more than half of men between ages 40 and 70 experience partial or complete ED, and approximately 10% have severe or complete ED (Feldman et al, 1994; Goldstein, Goren, Li, Tang, et al, 2019). Recent research has identified that there is a high prevalence of ED in young men (8% in men 20–30 years of age; Kessler et al, 2019).…”
Section: Burden Of Erectile Dysfunctionmentioning
confidence: 99%